The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s12649-018-00545-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Liquids from Slow Pyrolysis and Hydrothermal Carbonization in Plant Protection

Abstract: The feasibility of thermochemical biomass conversion technologies can be improved if value-added applications for all fractions can be developed. One of such approaches is the use of liquid by-products from slow pyrolysis and hydrothermal carbonization (HTC) in plant protection. Liquids produced from slow pyrolysis of pine bark, pine forest residues, wheat straw, and willow, and from hydrothermal carbonization of willow, were analyzed in this study. In particular, potential active compounds were analyzed, cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 33 publications
0
28
1
Order By: Relevance
“…As we predicted, the efficiency of PLM on weeds increased with increasing PL concentration and the results from the glasshouse, onion field and city park environments were consistent with each other. Hagner et al (2018) recently monitored the effectiveness of various slow pyrolysis liquids (pine, forest residues, wheat, willow) against snails, weeds and aphids and suggested that acids, and in particular the acetic acid, were the main reason for the observed pesticidal effects. In addition to the acetic acid, which has long been applied in plant protection as a herbicide (EPA, 2017; EU, 2017), other PL compounds such as furfural, formic acid, valeric acid, propanoic acid and some phenols were also reported to be effective in pest and weed control (Yatagai et al , 2002; Hensley and Burger, 2006; Hagner et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As we predicted, the efficiency of PLM on weeds increased with increasing PL concentration and the results from the glasshouse, onion field and city park environments were consistent with each other. Hagner et al (2018) recently monitored the effectiveness of various slow pyrolysis liquids (pine, forest residues, wheat, willow) against snails, weeds and aphids and suggested that acids, and in particular the acetic acid, were the main reason for the observed pesticidal effects. In addition to the acetic acid, which has long been applied in plant protection as a herbicide (EPA, 2017; EU, 2017), other PL compounds such as furfural, formic acid, valeric acid, propanoic acid and some phenols were also reported to be effective in pest and weed control (Yatagai et al , 2002; Hensley and Burger, 2006; Hagner et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Hagner et al (2018) recently monitored the effectiveness of various slow pyrolysis liquids (pine, forest residues, wheat, willow) against snails, weeds and aphids and suggested that acids, and in particular the acetic acid, were the main reason for the observed pesticidal effects. In addition to the acetic acid, which has long been applied in plant protection as a herbicide (EPA, 2017; EU, 2017), other PL compounds such as furfural, formic acid, valeric acid, propanoic acid and some phenols were also reported to be effective in pest and weed control (Yatagai et al , 2002; Hensley and Burger, 2006; Hagner et al , 2018). Hence, although the solid cover formed by the sticky PL and peat fibres likely suppressed weed growth by acting as a mechanical obstacle in our study, the weed‐inhibiting effect of PLM was most likely also based on the PL compounds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations